Cachexia and sarcopenia: mechanisms and potential targets for intervention. (June 2015) - Argilés, Josep M; Busquets, Silvia; Stemmler, Britta; López-Soriano, Francisco J
Highlights: Cachexia and sarcopenia share common trends: altered protein synthesis and degradation. Cachexia and sarcopenia are both driven by inflammation. Sarcopenia is ameliorated by resistance training, ingestion of AA, and testosterone. Cachexia is ameliorated by progestagens, corticosteroids, ghrelin agonists, myostatin antagonists and SARMs. Abstract : Cachexia is a multi-organ syndrome associated with cancer and other chronic diseases, characterized by body weight loss, muscle and adipose tissue wasting and inflammation, being often associated with anorexia. Skeletal muscle tissue represents more than 40% of body weight and seems to be one of the main tissues involved in the wasting that occurs during cachexia. Sarcopenia is a degenerative loss of skeletal muscle mass, quality, and strength associated with healthy ageing. The molecular mechanisms behind cachexia and sarcopenia share some common trends. Muscle wasting is the result of a combination of an imbalance between synthetic and degradative protein pathways together with increased myocyte apoptosis and decreased regenerative capacity. Oxidative pathways are also altered in skeletal muscle during muscle wasting and this seems to be a consequence of mitochondrial abnormalities that include altered morphology and function, decreased ATP synthesis and uncoupling. The aim of the present review is to analyse common molecular pathways between cachexia and sarcopenia in order to put forward potential targets for intervention.